Low frequency (1-Hz), right prefrontal repetitive transcranial magnetic stimulation (rTMS) compared with venlafaxine ER in the treatment of resistant depression: a double-blind, single-centre, randomized study - Bares, Martin; Kopecek, Miloslav; Novak, Tomas; Stopkova, Pavla; Sos, Peter; Kozeny, Jiri; Brunovsky, Martin; Höschl, Cyril (Journal of affective disorders, 2009)
BACKGROUND: Previous studies have shown effectiveness of repetitive transcranial magnetic stimulation (rTMS) in the treatment of depression. This double-blind study compared efficacy of l Hz rTMS over the right prefrontal dorsolateral cortex with venlafaxine ER in the treatment of resistant depression. METHODS: A total of 60 inpatients with depressive disorder (DSM-IV criteria), who previously did not respond to at least one antidepressant treatment, were randomly assigned to 1 Hz rTMS with placebo and venlafaxine ER with sham rTMS for 4 weeks. The primary outcome measure was score change in the Montgomery-Asberg Depression Rating Scale (MADRS). We also used Clinical Global Impression (CGI) and Beck Depressive. Inventory-Short Form (BDI-SF). The response was defined as a >or=50% reduction of MADRS score. RESULTS: There were no significant differences between treatment groups in MADRS (p=0.38), BDI-SF (p=0.56) and CGI (p=0.17) scores from baseline to endpoint. Response rates for rTMS (33%) and venlafaxine (39%) as well as remission (MADRS score<or=10 points) rates (19% vs. 23%) and drop-out rate did not differ between treatment groups. There were significant reductions of MADRS, CGI and BDI-SF scores in both groups. LIMITATIONS: Small sample size. No placebo arm was included for ethical reasons, because both treatments have previously been reported to be more effective than placebo. Relatively short duration of antidepressant treatment. CONCLUSION: The findings of this study suggest that, at least in the acute treatment, the right sided rTMS produces clinically relevant reduction of depressive symptomatology in patients with resistant depression comparable to venlafaxine ER. Larger sample sizes are required to confirm these results.
Keywords: Prefrontal Cortex; antidepresiva druhé generace; Humans; prefrontální mozková kůra; lidé středního věku; Personality Assessment; Cyclohexanols; Antidepressive Agents, Second-Generation; Double-Blind Method; Depressive Disorder, Major; Female; dospělí; dvojitá slepá metoda; lidé; transkraniální magnetická stimulace; testování osobnosti; Adult; depresivní porucha unipolární; ženské pohlaví; Male; Middle Aged; cyklohexanoly; Psychometrics; Transcranial Magnetic Stimulation; Venlafaxine Hydrochloride; venlafaxin hydrochlorid; mužské pohlaví; psychometrie